Phytochemical Screening and Pharmacological Evaluation of Merremia vitifolia (Burm.f.) Hallier f. Leaf Extract - Shorna, Mahabuba Khanam; Jannat, Sarah Waddun; Afrin, Syeda Rubaiya; Didari, Sayeda Saima; Islam, Mohammad Rashedul; Proma, Nawreen Monir; Hossain, Mohammed Kamrul (Chittagong University Journal of Biological Sciences, 2024)
The current investigation aimed to explore the various pharmacological properties of methanol extracts of Merremia vitifolia (Burm.f.) Hallier f. leaves (MEMV). Phytochemical analysis was performed following the established procedures. Using the hole board device, the anxiolytic action was measured. The oral glucose tolerance test (OGTT) was used to evaluate the hypoglycemic activity and the castor oil-induced diarrhea method was employed to explore the antidiarrheal activity in Swiss albino mice. Utilizing the brine shrimp lethality assay (BSLA), cytotoxicity was evaluated. In this study, it was observed that MEMV contained a number of active secondary metabolites such as triterpenes, alkaloids, glycosides, flavonoids, phenols and tannins. Compared to the control group, MEMV at 200 mg/kg and 400 mg/kg (p<0.05; p<0.001) significantly increased the number of head dips. However, MEMV showed potential as a dose-dependent anxiolytic medication. In the OGTT procedure, MEMV exhibited possible hypoglycemic effects that persisted for a shorter period. After 30 minutes of glucose load, the 200 mg/kg dose of MEMV significantly lowered blood glucose levels by 60.70% (p<0.001), in comparison to the control group. When compared to standard loperamide (p<0.001), the MEMV at both doses (200 mg/kg, 400 mg/kg) significantly (p<0.001) inhibited the total number of defecations during the testing period in the castor oil-induced antidiarrheal test. During the BSLA test, the LC50 values of MEMV were found to be 2.882 µg/mL. In comparison to the control group, MEMV demonstrated a good cytotoxic effect. To conclude, our research revealed that the plant extracts have potential anxiolytic, hypoglycemic, antidiarrheal, and cytotoxic properties. Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 35-44, 2024